Tri-mean-based statistical differential gene expression detection. (1st October 2012) - Ji, Zhaohua; Wu, Chunguo; Wang, Yao; Guan, Renchu; Tu, Huawei; Wu, Xiaozhou; Liang, Yanchun
Based on the assumption that only a subset of disease group has differential gene expression, traditional detection of differentially expressed genes is under the constraint that cancer genes are up- or down-regulated in all disease samples compared with normal samples. However, in 2005, Tomlins assumed and discussed the situation that only a subset of disease samples would be activated, which are often referred to as outliers.